Optimization of Tween 80 and Span 80 Combination in the Formulation of Niacinamide-Containing Body Lotion - Vica Aspadiah; Nur Illiyyin Akib; Astrid Indalifiany; Rahmat Muliadi; Reza Rosita Layuk (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
Body lotion is a liquid emulsion preparation consisting of an oil phase and a water phase stabilized by emulsifiers, functioning to maintain skin moisture and provide protection. One of the most widely used active ingredients in current cosmetic formulations is niacinamide, known for its effectiveness in brightening the skin, enhancing the skin barrier function, and reducing hyperpigmentation. The success of a body lotion formulation depends largely on the appropriate selection and concentration of emulsifiers to achieve emulsion stability and optimal physical characteristics. This study aimed to optimize the combination of Tween 80 and Span 80 emulsifiers in a body lotion formulation containing niacinamide using a 2² factorial design method with the assistance of Design-Expert software. The formulation was evaluated based on several physical parameters, including pH, adhesiveness, spreadability, viscosity, homogeneity, emulsion type, and physical stability, as well as a hedonic test assessing color, odor, and texture. Optimization results indicated that the best formulation was obtained from a combination of 1% Tween 80 and 10% Span 80. The resulting product had a pH of 6.4, adhesiveness of 112 seconds, spreadability of 6.1 cm, viscosity of 16,568.3 cps, good homogeneity, and demonstrated a stable oil-in-water (O/W) emulsion type without phase separation. Therefore, the optimum combination of Tween 80 and Span 80 in concentrations of 1% and 10%, respectively, yields a physically stable niacinamide-containing body lotion.